2020
DOI: 10.1108/jedt-07-2020-0294
|View full text |Cite
|
Sign up to set email alerts
|

High-performance computing for computational modelling in built environment-related studies – a scientometric review

Abstract: Purpose This paper aims to present the result of a scientometric analysis conducted using studies on high-performance computing in computational modelling. This was done with a view to showcasing the need for high-performance computers (HPC) within the architecture, engineering and construction (AEC) industry in developing countries, particularly in Africa, where the use of HPC in developing computational models (CMs) for effective problem solving is still low. Design/methodology/approach An interpretivism p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
(61 reference statements)
0
7
0
1
Order By: Relevance
“…Links connect two items. VOSviewer has been used for bibliometric study in similar studies in the DT era; for instance, Aghimien et al (2019Aghimien et al ( , 2020Aghimien et al ( , 2021, Chellappa et al (2021) andSafura Zabidin et al (2020) used it in the mapping industry 4.0 in the construction industry and digitalisation studies, workers health and safety, computational modelling, respectively. Visualisation has been popularly adopted in various construction industry research domains (Babalola et al, 2021;Mariam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Links connect two items. VOSviewer has been used for bibliometric study in similar studies in the DT era; for instance, Aghimien et al (2019Aghimien et al ( , 2020Aghimien et al ( , 2021, Chellappa et al (2021) andSafura Zabidin et al (2020) used it in the mapping industry 4.0 in the construction industry and digitalisation studies, workers health and safety, computational modelling, respectively. Visualisation has been popularly adopted in various construction industry research domains (Babalola et al, 2021;Mariam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although other databases such as Web of Science and Google Scholar were available, Scopus was chosen because of its broader scope (Hosseini et al , 2018). Scholars commonly use Scopus to collect literature (Guz and Rushchitsky, 2009), and it has been used in the majority of systematic review studies especially in built environment domain (Aghimien et al , 2020; Vigneshkumar and Salve, 2020; Nazir et al , 2020; Mariam et al , 2020; Aghimien et al , 2021; Vigneshkumar et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers [75][76][77][78][79][80][81] envision enhanced efficiency through smart technologies [75][76][77], smart grids [78], and AI-driven optimizations in industrial processes [79][80][81]. However, scholars [82][83][84][85][86][87] have focused on the energy intensity of digital technologies, with high-performance computing and data centers being potential culprits. Studies [88][89][90][91][92] have shown that digitalization facilitates the better integration of renewable energy into grids, promoting sustainability.…”
Section: Relationship Between Digitalization and Energy Consumptionmentioning
confidence: 99%